Fecal Transplantation Treatment of Antibiotic-Induced, Noninfectious Colitis and Long-Term Microbiota Follow-Up. (18th November 2014) - Satokari, Reetta; Fuentes, Susana; Mattila, Eero; Jalanka, Jonna; de Vos, Willem M.; Arkkila, Perttu
Abstract : Fecal microbiota transplantation (FMT) is an effective treatment for recurrent Clostridium difficile infection (CDI) and is considered as a treatment for other gastrointestinal (GI) diseases. We followed up the relief of symptoms and long-term, over-a-year microbiota stabilization in a 46-year-old man, who underwent FMT for antibiotic-induced, non-CDI colitis nine months after being treated for CDI by FMT. Fecal and mucosal microbiota was analyzed before the second FMT and during 14 months after FMT by using a high-throughput phylogenetic microarray. FMT resolved the symptoms and restored normal GI-function. Microbiota analysis revealed increased bacterial diversity in the rectal mucosa and a stable fecal microbiota up to three months after FMT. A number of mucosa-associated bacteria increased after FMT and some of these bacteria remained increased in feces up to 14 months. Notably, the increased bacteria included Bifidobacterium spp. and various representatives of Clostridium clusters IV and XIVa, such as Clostridium leptum, Oscillospira guillermondii, Sporobacter termitidis, Anaerotruncus colihominis, Ruminococcus callidus, R. bromii, Lachnospira pectinoschiza, and C. colinum, which are presumed to be anti-inflammatory. The presented case suggests a possible role of microbiota in restoring and maintaining normal GI-functionality and improves our knowledge on the etiology of antibiotic-induced, noninfectious colitis.